Pengaruh Beban Kerja Dan Lingkungan Kerja Non Fisik Terhadap Burnout Karyawan Pada PT. Wom Finance Di Tenggarong - Erna Putra Sari; Johansyah Johansyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract The purpose of this study was to determine whether the variable workload and non-physical work environment had a significant effect on employee burnout at PT. WOM. Finance in Tenggarong and to find out, of the two variables, which variable has the greatest influence on employee burnout at PT. WOM. Finance in Tenggarong. The results of the calculation of the F test, workload variables (X1) and non-physical work environment (X2) simultaneously affect employee burnout, so the first hypothesis accepted and proven to be true. From the two results of the partial correlation test, it can be seen that the value of the workload variable is the largest compared to the non-physical work environment variable, so the workload variable is The most dominant variable affects employee burnout. From this description, it can be concluded that the second hypothesis in this study is "That, the workload variable has the most dominant influence on employee burnout at PT. WOM. Finance in Tenggarong." accepted and proven to be true. The partial test results show that the workload and non-physical work environment variables have a positive and significant effect on employee burnout Keywords: Workload, Non-physical Work Environment, Work Saturation